The Effects of the Respiratory Rehabilitation Program on Perceived Self-Efficacy and Dyspnea in Patients with Lung Cancer - Pramote Saetan; Suchira Chaiviboontham; Piyawan Pokpalagon; Pichai Chansriwong (Elsevier, 2020)
Purpose: This study aims to examine the effects of the respiratory rehabilitation program on perceived self-efficacy and dyspnea in patients with lung cancer. Methods: This is a quasi-experimental research study with a two-group repeated measures design with the pretest and post-test at Week 4 and Week 8. The theory of self-efficacy by Bandura was used as the conceptual framework. The sample consisted of patients with non-small-cell lung cancer Stage 4 who visited the oncology clinic in a university hospital. Twenty-eight patients were enrolled and equally allocated to the control group and experimental group. The control group received routine nursing care only, whereas the experimental group received the respiratory rehabilitation program. The program comprised dyspnea educating, breathing exercise, using handheld fans, effective coughing, respiratory strengthening training, and follow-up by phone in the third and sixth week. Data for perceived self-efficacy and dyspnea were collected before the program start and reassessment in the fourth and eighth week. Instrumentation was composed of the respiratory rehabilitation program, demographic data, perceived self-efficacy assessment for respiratory rehabilitation, and the Cancer Dyspnea Scale. Data were analyzed using descriptive statistics and one-factor repeated measures analysis of variance and by comparing means between groups. Results: The result revealed that almost all of the patients in the sample were men, and the mean age of the experimental group and control group was 65.80 years (standard deviation = 8.80) and 73.00 years (standard deviation = 7.60), respectively. There was significant different in the mean score of perceived self-efficacy and dyspnea between the experimental group and the control group (p < .050). Conclusion: Based on the findings of the study, the respiratory rehabilitation program should be used to promote self-efficacy and relieve dyspnea in patients with lung cancer.